Dyeing Properties and Analysis by RP-HPLC-DAD of Silk Fibers Dyed with Weld (Reseda luteola L.) and Walloon Oak (Quercus ithaburensis Decaisne) - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2011)
The purpose of this study is to analyse and to determine their colour values and rubbing and light fastness properties of the silk fabrics dyed with the natural dyes present in weld (Reseda luteola L.) and walloon oak (Quercus ithaburensis Decaisne). A reversed-phase high performance liquid chromatography (RP-EIPLC) with diode-array detection (DAD) method was utilized for the identification of natural dyes present in the dyed silk fabrics. The extraction of dyes from the silk fabrics was carried out with 37 % hydrochloric acid/methanol/water mixture (2/1/1 v/v/v). CIEL*a*b* and fastness values of the fabrics were determined. In the study reported here, for the analysis and the dyeing of silk fabrics an analytical method was developed.
Keywords: Weld; Walloon oak; Natural dyeing; Fastness; HPLC; CIEL*a*b*; LIQUID-CHROMATOGRAPHY; NATURAL DYES; IDENTIFICATION; PIGMENTS; FLAVONOIDS; DYESTUFFS